Spatial Analysis of Access to Drinking Water for the Populations of the Lobo Watershed in Nibéhibé (Central-Western Côte d'Ivoire) - TOURE , Fanraban Fabrice; KONAN-WAIDHET, Arthur Brice; YAO , Affoue Berthe; DIARRA, Ali; KOUA, Tanoh Jean Jacques (European Journal of Applied Sciences, 2022)
Water is a limited natural resource, necessary for life and ecological systems, and essential for economic and social development. Therefore, the need for water is increasing. This observation makes sense in developing countries in general and more particularly in Côte d'Ivoire at the level of the Lobo watershed. Indeed, despite the efforts made by the state authorities to build water infrastructure, a large majority of the population in rural areas still does not have access to drinking water. This manuscript addresses the problem of financial difficulties related to access to water in the Lobo basin in Nibéhibé. The objective of the study is to highlight the difficulties of sustainable access to drinking water for the populations of the Lobo watershed in Nibéhibé. To achieve this objective, the methodology was based on the triptych documentary research, interview and survey by questionnaire. The documentary research consisted in defining the contours of the subject to better understand it. Then, the interviews conducted with the actors of the water sector in the Lobo River Basin made it possible to collect information on their level of involvement and responsibility at the economic level in the sustainable access to water in the basin. Finally, using the simple random choice method without discount and a statistical equation, we surveyed 300 households in three departments (Daloa, Vavoua and Zoukougbeu). The population surveys, combined with spatially referenced data in a GIS, allowed us to assess not only the spatial distribution of water supply sites, but also to evaluate the state of functionality of the hydraulic structures. The results show that despite all the actions undertaken by the Ivorian State and SODECI for the supply of drinking water, the populations still have difficulties with sustainable access to water resources. This situation will lead the population to turn to other sources of water supply. Unfortunately, these water access strategies are costly and put people at risk.